Medical image analysis using deep learning: a review - Nisa, Syed Qamrun; Ismail, Amelia Ritahani; MD Ali, M. A. B.; Khan, Mohammad Shadab (IEEE, 2019)
Over the recent past, deep learning is one of the core research directions which has gained a great deal of attention due to its outstanding performance in the area of medical image analysis. This paper aims to present a review of deep learning concepts related to medical imaging. We examine the use of deep learning for medical image analysis including segmentation, object detection and classification. Deep learning techniques including convolutional neural networks (CNNs), recurrent neural network (RNNs) and auto-encoder (AE) are also discussed in this paper.